2021
DOI: 10.1021/acssuschemeng.1c02278
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Process of Monoethanolamine-Based CO2 Absorption and CO2 Mineralization with SFGD Slag: Process Simulation and Life-Cycle Assessment of CO2 Emission

Abstract: Integrated CO 2 absorption and mineralization (IAM) is a promising approach to fix CO 2 in a far less energyintensive way. The semidry flue gas desulfurization (SFGD) slag containing a considerable amount of Ca(OH) 2 is potential for mineralizing CO 2 . In this work, an IAM process combining monoethanolamine (MEA)-based CO 2 absorption and mineralization with SFGD slag is proposed and investigated to provide a systematical evaluation of the net CO 2 fixation. A desorption efficiency of 68% and an entrainment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…We also scaled up this process in a 20 L reactor, and the results were comparable to those of the 300 mL scale, and further development is required to improve the quality of the products. Furthermore, we plan to reuse and recycle the liquid used in the dissolution and carbonation process, and the salts will be concentrated by multiple cycles, which can be precipitated by adding ethanol or implementing electrolysis to get the required acid and base. In future, we will optimize the integrated process to get a more sustainable and cost-effective process by applying life cycle assessment (LCA) and technoeconomic assessment (TEA) . According to our preliminary results of TEA, it shows that the cost of acid and base supply and the revenue from products are the most critical factors, and we will conduct a detailed assessment to carry out the sensitivity analysis of various effects on the CO 2 emissions and CO 2 avoidance cost.…”
Section: Discussionmentioning
confidence: 99%
“…We also scaled up this process in a 20 L reactor, and the results were comparable to those of the 300 mL scale, and further development is required to improve the quality of the products. Furthermore, we plan to reuse and recycle the liquid used in the dissolution and carbonation process, and the salts will be concentrated by multiple cycles, which can be precipitated by adding ethanol or implementing electrolysis to get the required acid and base. In future, we will optimize the integrated process to get a more sustainable and cost-effective process by applying life cycle assessment (LCA) and technoeconomic assessment (TEA) . According to our preliminary results of TEA, it shows that the cost of acid and base supply and the revenue from products are the most critical factors, and we will conduct a detailed assessment to carry out the sensitivity analysis of various effects on the CO 2 emissions and CO 2 avoidance cost.…”
Section: Discussionmentioning
confidence: 99%
“…11 Extensive studies have demonstrated that compared to conventional CO 2 absorption and thermal regeneration technologies, IAM could achieve a larger regeneration efficiency and lower regeneration energy. [9][10][11][12][13][14][15][16][17][18][19] For example, previous studies reported that similar monoethanolamine (MEA) regeneration efficiencies (about 40%) were obtained through CaO-mediated IAM and traditional thermal regeneration. However, the later required >3.0 MJ/kg-CO 2 heat input while nearly zero additional heat was required for the IAM due to its thermodynamically downhill carbonation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1). 11 Extensive studies have demonstrated that compared to conventional CO 2 absorption and thermal regeneration technologies, IAM could achieve a larger regeneration efficiency and lower regeneration energy 9–19 . For example, previous studies reported that similar monoethanolamine (MEA) regeneration efficiencies (about 40%) were obtained through CaO‐mediated IAM and traditional thermal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Liu et al 21 reported a single-step direct aqueous carbonation method for CaO and CaSiO 3 , which was based on the use of sodium glycinate. This method adopted the integrated CO 2 absorption and mineralisation (IAM) technology, 22,23 which could reduce the energy consumption of glycinate regeneration through a chemical method instead of the traditional thermal method (i.e., eqn (3)-( 6)). According to their study, as shown in eqn (1), the dissolved CO 2 reacts with glycinate to generate the corresponding carbamate and zwitterionic ion.…”
Section: Introductionmentioning
confidence: 99%